Kebijakan Indonesia dan Fiji Menyepakati Perjanjian Kerja Sama di Bidang Pertahanan - Sofia Naliza Sitepu; Rafa Shabirah; Tamaulina Br.Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
This research analyzes the policy of the defense cooperation agreement between Indonesia and Fiji, which aims to increase military capabilities and strengthen stability and security in the Pacific and Southeast Asia regions. This agreement includes joint training, exchange of intelligence information, and transfer of military technology. The research results show that this cooperation provides various significant benefits, including increased military preparedness and closer diplomatic relations. However, implementing this agreement faces a number of challenges such as differences in military culture, logistical constraints and budget limitations. To overcome these obstacles, recommended strategies include increasing dialogue and communication, developing infrastructure and technology, and optimizing the use of budgets and resources. By implementing these suggestions, it is hoped that defense cooperation between Indonesia and Fiji can continue to develop and make a positive contribution to regional security and stability.